2016
DOI: 10.1371/journal.pone.0155237
|View full text |Cite
|
Sign up to set email alerts
|

Human Exposures to Bisphenol A, Bisphenol F and Chlorinated Bisphenol A Derivatives and Thyroid Function

Abstract: Although the increasing prevalence of thyroid nodular disease (TND) has been partially attributed to the more frequent usage of improved diagnostics, environmental factors, such as exposures to thyroid-disrupting chemicals may contribute to TND and altered thyroid function. We investigated the association between exposures to bisphenol A (BPA), its chlorinated derivatives (ClxBPA), and bisphenol F (BPF) with TND and thyroid measures in adult women. A case-control study in Cyprus and Romania (n = 212) was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 32 publications
6
37
0
Order By: Relevance
“…In the cohort of adult women evaluated, although urinary BPA concentrations and serum TSH values resulted significantly associated no relationship was found with the prevalence of thyroid nodular disease [31].…”
Section: Industrial Chemicalsmentioning
confidence: 79%
See 1 more Smart Citation
“…In the cohort of adult women evaluated, although urinary BPA concentrations and serum TSH values resulted significantly associated no relationship was found with the prevalence of thyroid nodular disease [31].…”
Section: Industrial Chemicalsmentioning
confidence: 79%
“…[30] Evaluated the association between thyroid nodular disease and BP-A and -F In the cohort of adult women evaluated, urinary concentration of BPA and serum TSH value were significantly positively associated, but no association was found with the nodular disease [31] Abbreviations: PCBs: Polychlorinated Biphenyls; TT3: total triiodothyronine; TT4: total thyroxin; T4: thyroxin; T4S: thyroxin sulfate: T3: triiodothyronine; rT3: reverse triiodothyronine; TSH: thyroid stimulating hormone; TBG: thyroxine-binding globulin; FT4: free thyroxin; OH-PCB: hydroxylated -Polychlorinated Biphenyls; FT3: free triiodothyronine; TH: thyroid hormones; PBDE: Polybrominated Diphenyl Ethers; NIS: sodium-iodine symporter; BP-A: Bisphenol-A.…”
Section: Bisphenol-a Phthalatesmentioning
confidence: 99%
“…Other studies, with different population segments, such as Chinese adults, workers with occupational BPA exposure, men from a fertility clinic, and women with polycystic ovary syndrome all showed similar thyroid profiles, with increased TH levels and/or reduced TSH levels linked to BPA exposure (Meeker et al 2010, Wang et al 2012, Vahedi et al 2016. By contrast, other studies showed positive correlations between urinary BPA and TSH levels (Geens et al 2015, Andrianou et al 2016. There is no consensus in the literature regarding phthalate exposure in male populations, with studies showing an inverse association between MEHP and free T4 and T3 levels (Geens et al 2015, Andrianou et al 2016Meeker et al 2007 and another showing no disruption of TH levels in young males exposed to MEP and MBP (Janjua et al 2007).…”
Section: Plasticizersmentioning
confidence: 92%
“…A South Korean cross-sectional study in adults (M, n=2638; F, n=3365; adults age >19 years) reported a negative correlation between u-BPA and serum TSH levels, but not with serum levels of total T4 or T3 25 [86]. In contrast, a smaller case-control study of thyroid nodular disease in women from Cyprus and Romania (n=212; age 47 and 52 years, respectively) found a positive relation between u-BPA and serum TSH levels by multivariate analyses 26 [87]. The authors reported that plastic bottled water and personal care products usage were significant predictors of spot u-BPA levels.…”
Section: Human Studies; Associations Between U-bpa Levels and Thyroidmentioning
confidence: 94%